Enhancement of brillouin stokes generation in the s-band region using a combination s-band depressed cladding erbium Doped fiber and semiconductor optical amplifier - Ahmad, Harith; Zulkifli, Mohd Zamani; Hassan, N. A.; Harun, Sulaiman Wadi (Pleiades Publishing, Ltd, 2012)
A hybrid DepressedCladding Erbium Doped Fiber (DCEDF) together with a broadband Semi conductor Optical Amplifier (SOA) to enhance the generation of Stokes and antiStokes in a 7.7 km long Dis persion Compensating Fiber (DCF) is proposed and demonstrated. The performance of the proposed system is compared against that of a conventional system with only the DCEDF as the gain medium, and the incor poration of the SOA can be seen to enhance the generation of Brillouin Stokes significantly. The proposed system is able to generate an output comb with a flattop and more than 29 Stokes and 13 antiStokes lines, an increase of 14 and 8 lines respectively over the conventional system and covering the entire Sband region. The output comb generated is highly stable over time.